A prospective study of the impact of fluorodeoxyglucose positron emission tomography with concurrent non‐contrast CT scanning on the management of operable pancreatic and peri‐ampullary cancers. Issue 7 (July 2015) - Burge, Matthew E.; O'Rourke, Nick; Cavallucci, David; Bryant, Richard; Francesconi, Alessandra; Houston, Kathleen; Wyld, David; Eastgate, Melissa; Finch, Robert; Hopkins, George; Thomas, Paul; Macfarlane, David
Abstract: Background: The role of fluorodeoxyglucose (FDG) positron emission tomography (PET/CT) scanning in operable pancreas cancer is unclear. We, therefore, wanted to investigate the impact of PET/CT on management, by incorporating it into routine work‐up. Methods: This was a single‐institution prospective study. Patients with suspected and potentially operable pancreas, distal bile duct or ampullary carcinomas underwent PET/CT in addition to routine work‐up. The frequency that PET/CT changed the treatment plan or prompted other investigations was determined. The distribution of standard uptake values (SUV) among primary tumours, and adjacent to biliary stents was characterised. Results: Fifty‐six patients were recruited. The surgical plan was abandoned in 9 (16%; 95% CI: 6–26) patients as a result of PET/CT identified metastases. In four patients, metastases were missed and seven were inoperable at surgery, not predicted by PET/CT. Unexpected FDG uptake resulted in seven additional investigations, of which two were useful. Among primary pancreatic cancers, a median SUV was 4.9 (range 2–12.1). SUV was highest around the biliary stent in 17 out of 28 cases. PET/CT detected metastases in five patients whose primary pancreatic tumours demonstrated mild to moderate avidity (SUV < 5). Conclusions: PET/CT in potentially operable pancreas cancer has limitations. However, as a result of its ability to detect metastases, PET/CT scanning is a useful tool in the selection of such patients for surgery.